Impact of maternal hypothyroidism on fetal thyroid gland: a prospective observational study - Xinyuan Feng; Huijie Sun; Tianci Liu; Liang Li (BMC Pregnancy and Childbirth)
Abstract Background Maternal hypothyroidism has been associated with impaired offspring neurodevelopment but the underlying mechanisms are unclear now. We hypothesize that maternal hypothyroidism influences the development of fetal hypothalamic-pituitary-thyroid (HPT) axis, and thereby indirectly affects postnatal cognitive development. Methods This prospective observational study included singleton pregnancies with hypothyroidism before 14 weeks of gestation. Ultrasound measurements of fetal thyroid size were performed at 20–24 and 28–32 weeks. The primary outcome was fetal thyroid volumes at two time points; and the secondary outcomes were pregnancy and neonatal outcomes, including birthweight, delivery weeks, preterm birth, stillbirth or miscarriage, and neonatal thyroid functions on the third postnatal day. Results A total of 136 women participated in this study, comprising 68 with hypothyroidism and 68 with uncomplicated pregnancies. There was no significant difference between the hypothyroidism and control group of fetal thyroid volumes measured at gestation of 20–24 weeks (230.58 ± 63.75mm3 vs. 230.15 ± 75.69mm3, P = 0.98) and 28–32 weeks (491.55 ± 154.88mm3 vs. 450.16 ± 136.13mm3, P = 0.059). Additionally, the incidence of adverse events was also similar between groups. These findings remained unchanged after adjusting for confounding factors. Conclusions The results of this study suggest that maternal hypothyroidism may not significantly influence the fetal HPT axis. However, it is important to emphasize that this conclusion is based solely on data from mothers with well-controlled hypothyroidism. Moreover, the small prevalence of overt clinical hypothyroidism should be considered when interpreting this finding.